Peran Kepemimpinan Kepala Sekolah dalam Meningkatkan Penerimaan Peserta Didik Baru SMK Muhammadiyah Imogiri: PERAN KEPEMIMPINAN KEPALA SEKOLAH (TIRAI: Jurnal Program Studi Manajemen Pendidikan Islam, 2023)
This study aims to find out and describe in full the role of the principal in increasing new student acceptance at Muhammadiyah Imogiri Vocational School. The qualitative descriptive method was used in this study to determine the role of the principal in increasing new student admissions. Data collection techniques included documentation, observation, and interview techniques, which were used by interviewing school principals, deputy principals, and heads of expertise programs. The results of this study found that the role of the principal in increasing the acceptance of new students at Muhammadiyah Imogiri Vocational School was very visible from his role as a manager by appointing teachers with the right position in the team, then his role as an administrator, namely carrying out planning and assignments according to the rules; as a supervisor, the principal always checks and evaluates the stages in increasing the acceptance of new students; and as a leader, the principal provides encouragement, direction, and motivation in carrying out the new student admissions program. The principal encounters several obstacles, namely school infrastructure, teacher loyalty, and school resources. The principal seeks to increase the acceptance of new students by maximizing their human resources.